1975
DOI: 10.1002/jsfa.2740260918
|View full text |Cite
|
Sign up to set email alerts
|

The digestion of the lipids of processed red clover herbage by sheep

Abstract: Three mature wether sheep, equipped with re-entrant cannulae at the proximal duodenum and terminal ileum were fed either frozen, or dried and chopped or dried and ground red clover herbage, and samples of duodenal and ileal digesta and faeces were collected. Analysis of the feed and digesta samples for their individual long chain fatty acid content enabled the quantitative digestion of herbage lipids to be investigated.The flow of total fatty acids into the small intestine was greater than the amount daily con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…In all periods examined, fatty acid flows into the duodenum were less than corresponding dietary intakes (-15.7 to -32.6% of intake) except in the stemmy regrowth where positive flows were noted (+11.2-20.2%). Similar observations were noted by Outen et al [23] in sheep fed red clover and suggestions of negative fatty acid balances across the rumen in sheep fed fresh forage were reported by Ulyatt and MacRae [30]. In studies with silage Lee et al [15] found positive flows for grass and mixtures of grass and clover but negative flows for pure clover diets.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In all periods examined, fatty acid flows into the duodenum were less than corresponding dietary intakes (-15.7 to -32.6% of intake) except in the stemmy regrowth where positive flows were noted (+11.2-20.2%). Similar observations were noted by Outen et al [23] in sheep fed red clover and suggestions of negative fatty acid balances across the rumen in sheep fed fresh forage were reported by Ulyatt and MacRae [30]. In studies with silage Lee et al [15] found positive flows for grass and mixtures of grass and clover but negative flows for pure clover diets.…”
Section: Discussionsupporting
confidence: 78%
“…Relative to intake, flow was increased on the control treatment by 20.9 g per d (17.9% increase) but was reduced on the HS treatment by 35.4 g per d (17.6% reduction). Negative flows of fatty acids are sometimes observed when supplementing with lipids [6,16,34] or with fresh forages [23,30] suggesting losses due to absorption across the rumen wall and/or microbial degradation to other compounds. Others, however, have reported positive flows in response to feeding lipids to steers [29] or sheep [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feeding of both grass silages resulted in a net synthesis of total fatty acids from mouth to duodenum, whereas red clover silage and the mixtures all resulted in a net loss of total fatty acids, with duodenal flows 1.12, 1.02, 0.94, 0.93, and 0.86 times fatty acid intake for high-sugar grass, control grass, high-sugar grass/ red clover mix, control grass/red clover mix, and red clover silages, respectively. This trend has previously been reported with grass and clover silages (Outen et al, 1975;Lee et al, 2003a) and harvested grass (Bauchart et al, 1984;Scollan et al, 2003). This may in part be the result of different microbial populations on the different diets, which through their different microbial lipid content may result in changes in net lipid flow to the duodenum (Merry and MacAllan, 1983).…”
supporting
confidence: 74%
“…Despite this interest, the real challenge to the ruminant nutritionist has been to reduce biohydrogenation to retain PUFA and hence increase the health value of ruminant fat (Tapiero et al, 2002). The few studies that reported on lipid metabolism of complete forage diets indicate extensive biohydrogenation of C18:2n-6 and C18:3n-3 (Outen et al, 1975;Bauchart et al, 1984;Scollan et al, 2003). Lee et al (2003a) investigated the effect of clover silages (red vs. white and in combination with grass) on ruminal metabolism of forage lipids.…”
Section: Introductionmentioning
confidence: 99%